Electron Transport Assisted by Transparent Conductive Oxide Elements in Perovskite Solar Cells. Issue 3 (27th December 2021) - Zhang, Wenqi; Lin, Zhichao; Cai, Qingbin; Xu, Xiangning; Dong, Hongye; Mu, Cheng; Zhang, Jian‐Ping
Abstract: Fluorine and indium elements in F‐doped SnO2 (FTO) and Sn‐doped In2 O3 (ITO), respectively, significantly contribute toward enhancing the electrical conductivity of these transparent conductive oxides. In this study, fluorine was combined with indium to modify the SnO2 electron transport layer (ETL) through InF3 . Consequently, the modified perovskite solar cells (PSCs) showe the favorable alignment of energy levels, improved absorption and utilization of light, enhanced interfacial charge extraction, and suppressed interfacial charge recombination. After InF3 modification, the open circuit voltage ( V oc ) and fill factor (FF) of the PSC were significantly improved, and the photoelectric conversion efficiency (PCE) reached 21.39 %, far exceeding that of the control PSC (19.62 %). Abstract : Fine performance : The modification of SnO2 electron transfer layers by F in fluorine‐doped tin oxide and In in indium tin oxide together can substantially improve the performance of perovskite solar cells by optimizing the energy level alignment and enhancing the interfacial charge carrier extraction.